Ukraine in Modern International Relations: Eurasian Paradigm - Khvist, Victoria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article covers the main principles of foreign policy at the beginning of independence and their consistent implementation in Ukraine's practical activities in the coming years. The main focus is on the characteristics of the Eurasian vector, especially on the development of mutually beneficial cooperation with neighboring countries and, first of all, with Russia.
Keywords: foreign policy; international law; geopolitics; Ukraine and Russia; geostrategy; crisis phenomena; democracy